Concentration of Selenium and Mercury in six species of fishes from Shatt Al-Arab River, Iraq - Abdulsahib, Hassan T.; Mohammed, Sarmad G.; Mohammed, Jenan J.; Awad, Nadhum A.N. (Iraqi Journal of Aquaculture, 2022)
The present study deal with determination of Se:Hg ratio in six fish species collected from Shatt Al-Arab river during the period June 2010 to Augest 2010. Muscles of the most important six commercial species of fish C. Carpio, B. luteus, L. abu, T. zilli, B. sharpeyi and T. ilisha have been analyzed after wet digestion with a mixture of concentrated acids (HClO4 / HNO3).The obtained results show that L. abu species having the highest Se:Hg ratio, while B. luteus species having the lowest Se:Hg ratio. Tissues analysis (skin, gills, kidney, liver, muscles) of B. sharpeyi reveals that skin accumulates the highest Se:Hg ratio levels, while muscles contained the lowest Se:Hg ratio. The values obtained are compared with literature data and selenium contents in fish muscle.